Tata Kelola Lingkungan di Indonesia: Peran Muhammadiyah, Intervensi Negara, dan Dinamika Praktik Hukum - Wahdini, Muhammad; Kamsi, Kamsi; Hasse Jubba (Universitas Islam Negeri Antasari Banjarmasin, 2024)
The study explores the causes of the controversy between the Muhammadiyah and the State in the policy of ecological law in Indonesia. The exploration uses methods of normative law research with conceptual approaches and philosophy of law. The results of this study show that the contestation of the Muhammadiyah and the State in ecological law politics in Indonesia is caused by the first factor of epistemological differences in legal policy, the epistemology of Muhammadiyah in line with the Islamic ecological concepts of Tauhid, Khilafah, Amanah, Halal Haram, Balance and Misconduct. This epistemology differs from what the state practices, namely industrialization, which is reflected in the birth of some legislative regulations that are considered ecologically unfair. Both paradigm differences, Muhammadiyah advances theoantroposentrism. As God's representative on earth, Muhammadiyah takes precedence over a prophetic perspective. The State paradigm also in practice needs to industrialize for economic growth, so that in practice there is controversy in legal politics. In practice, the controversy led to a change in the political direction of ecological law in Indonesia as Muhammadiyah succeeded in conducting judicial review, criticizing state policy to advocating the law against societies in conflict ecological sector